TEKNIK MODELING UNTUK MENGURANGI SELF INJURIOUS BEHAVIOR PADA ANAK AUTIS: TINJAUAN LITERATUR SISTEMATIS - Hasanah. Z, Afifa; Johandri Taufan; Rahmahtrisilvia; Endang Sri Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Self injurious behavior (SIB) is one of the most critical behavioral challenges in children autism spectrum disorder (ASD), affecting their safety, social participation, and academic outcomes. This study combines a Systematic Literature Review (SLR) using the PRISMA framework with bibliometric analysis to examine the effectiveness, types, and success factors of modeling techniques in reducing SIB among children with autism. A bibliometric analysis using VOSviewer and Bibliometrix was conducted on 257 documents from 171 sources spanning 2016-2026, drawn from the Scopus database. After rigorous PRISMA screening, 11 studies were included in the final synthesis. Bibliometric findings reveal that the USA dominates research output, and key themes cluster around autism spectrum disorder, behavioral intervention, and video modeling. The annual scientific production shows a peak around 2023-2024, with a slight decline in 2025-2026. SLR findings confirm that video modeling and video self modeling are the most effective techniques for reducing SIB. Success factors include functional behavior assessment, parental involvement, technology accessibility, and psychosocial environment quality. These findings provide an evidence-based foundation for developing adaptive, technology assisted behavioral interventions in special and inclusive education settings.